If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -1(-4) = 4 Multiply -1 * -4 x + 4 = 4 Reorder the terms: 4 + x = 4 Add '-4' to each side of the equation. 4 + -4 + x = 4 + -4 Combine like terms: 4 + -4 = 0 0 + x = 4 + -4 x = 4 + -4 Combine like terms: 4 + -4 = 0 x = 0 Solving x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Simplifying x = 0
| 6.7+1.3n=3.19 | | -4(8-m)=-4(1-8m) | | 2.5x+7.5=32.5 | | 0=6x^2+10x+2 | | 11x+27=5x+33 | | 4p-6p=2(8p-3)-8(5p+2) | | 2(7+b)=42 | | Y=ln(x+1)+4 | | 3(7+B)=90 | | -7(1+2m)=-5(2m-5) | | 5/3/4/5+3/2x2/3 | | 13x+21=4x+12 | | -5a-6(1-5a)=2-(2a+8) | | x^2-2x+12=3x+36 | | -36x^2+144x-60=0 | | (m-15)(m+9)=m-15 | | -(5+3p)-6p=-4(p+2)-7 | | (y-8)(y+2)=y-8 | | 0.4/a=0.32 | | 7x-8=3x-40 | | 3a+(a+b)=180 | | a+3a+(a+b)=180 | | 1.5(x-1)-1.5=2.5(x-3) | | -8(4n+8)-2(1-3n)=-n+8+n+4 | | -2+2(6)= | | -4r+8=32 | | -3p+3p=-6(5p+1)+6(3+7p) | | -4.8/-1.6 | | -5(6p+8)+6(p-7)= | | -7/8x=-21/32 | | 4q-3.3=2.4q+10.78 | | 7(2x+3)+8=-6(7x+4)+3x |